Co-detection of respiratory syncytial virus with other respiratory viruses across all age groups before and during the COVID-19 pandemic - Hayek, Haya; Amarin, Justin Z.; Qwaider, Yasmeen Z.; Khanfar, Asim; Stopczynski, Tess; Schmitz, Jonathan; Chappell, James D.; Wrenn, Jesse O.; Spieker, Andrew J.; Halasa, Natasha B.; Howard, Leigh M. (Frontiers in Virology, 2023)
Background: Patterns of respiratory syncytial virus (RSV) co-detection with other viruses may have been disrupted during the coronavirus disease 2019 (COVID-19) pandemic, but the clinical impact of viral co-detections with RSV is not well-established. We aimed to explore the frequency and clinical outcomes associated with RSV single detection and co-detection before and during the pandemic. Methods: We conducted a single-center retrospective cohort study of all children and adults with respiratory samples tested using a respiratory pathogen panel (RPP; 01/01/2018–11/30/2022), a provider-ordered polymerase chain reaction–based assay that detects respiratory pathogens. We stratified our cohort into age groups: 0–4, 5–17, 18–64, and ≥65 years old. Among RSV-positive samples, we compared the proportion of samples with single RSV detection before and during the pandemic and the patterns of specific viral co-detections. We compared the odds of hospitalization, oxygen use, intensive care unit admission, and intubation between individuals with RSV single detection and those with co-detection. Results: Among 57,940 samples collected during the study period, 3,986 (6.9%) were RSV-positive. RSV was co-detected with at least one other virus in 1,231/3,158 (39.0%), 104/348 (29.9%), 49/312 (15.7%), and 21/168 (12.5%) of samples from individuals 0–4, 5–17, 18–64, and ≥65 years old, respectively. The relative frequencies of RSV single detection and co-detection were comparable before and during the pandemic except in children 0–4 years old, in whom single RSV detections were more prevalent before (63.7%) than during (59.5%) the pandemic (p=0.021). In children 0–4 years old, RSV co-detection was associated with lower odds of hospitalization compared to single RSV detection, and RSV co-detection with parainfluenza viruses or human rhinovirus/enterovirus was associated with significantly lower odds of hospitalization, while RSV/SARS-CoV-2 co-detection was associated with higher odds of ICU admission. In adults ≥65 years old, RSV co-detection was associated with lower odds of oxygen use. Conclusion: The proportion of RSV co-detection did not appreciably vary before and during the pandemic, except in young children, though the combinations of co-detected viruses did vary. Our findings suggest that the clinical impact of RSV co-detection with other viruses may be age-associated and virus-specific.